2013
DOI: 10.1073/pnas.1300532110
|View full text |Cite|
|
Sign up to set email alerts
|

NF-κB inhibits osteogenic differentiation of mesenchymal stem cells by promoting β-catenin degradation

Abstract: Mesenchymal stem cell (MSC)-based transplantation is a promising therapeutic approach for bone regeneration and repair. In the realm of therapeutic bone regeneration, the defect or injured tissues are frequently inflamed with an abnormal expression of inflammatory mediators. Growing evidence suggests that proinflammatory cytokines inhibit osteogenic differentiation and bone formation. Thus, for successful MSC-mediated repair, it is important to overcome the inflammation-mediated inhibition of tissue regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
239
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(268 citation statements)
references
References 57 publications
15
239
1
1
Order By: Relevance
“…30 Previous reports suggested that TNF-a enhances osteoclastogenesis and inhibits osteogenesis at an early stage of inflammation, but induces osteogenesis at the later tissue repair stages of inflammation. 30 The role of NF-kB in osteogenesis in previous reports [31][32][33][34][35] and our current findings may be due to different time points of evaluation, different proinflammatory stimuli, and the specific osteogenic markers tested.…”
Section: Figmentioning
confidence: 61%
See 2 more Smart Citations
“…30 Previous reports suggested that TNF-a enhances osteoclastogenesis and inhibits osteogenesis at an early stage of inflammation, but induces osteogenesis at the later tissue repair stages of inflammation. 30 The role of NF-kB in osteogenesis in previous reports [31][32][33][34][35] and our current findings may be due to different time points of evaluation, different proinflammatory stimuli, and the specific osteogenic markers tested.…”
Section: Figmentioning
confidence: 61%
“…36 In other studies, the suppression of NF-kB promoted osteogenesis in primary bone marrow-derived MSCs and conditional NF-kB-deficient mice. 31 The suppressive effects of NF-kB on osteogenesis are mediated by direct upregulation of Smurf1/2 expression to enhance b-catenin degradation. 31 On the contrary, Cho et al demonstrated that NF-kB activated by TNF-a promoted osteogenesis through upregulation of a transcriptional coactivator with PDZ-binding motif (TAZ) in adipose-derived MSCs.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, it was shown in a murine model that upon biomaterial subcutaneous implantation there is first recruitment of inflammatory cells, which is then correlated with recruitment of MSC [4][5][6][7]. MSC recruitment can then lead to subsequent modulation of inflammation and is essential to promote the constructive remodelling of the tissue [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…13 Meanwhile, IL-17 stimulates the nuclear factor kappa B (NF-κB) signaling pathway and impairs the differentiation of BMMSCs. 15 Therefore, defining the crosstalk between proinflammatory cytokines and BMMSCs is an important goal of the newly emerging osteoimmunology field, and such insights may also be helpful for designing improved protocols for BMMSC-mediated bone repair and regeneration.…”
mentioning
confidence: 99%